Effects of Antisite Defect Density on Crystal and Electronic Structures of Monolayer Hexagonal Boron Nitride. Issue 9 (11th July 2021) - Ding, Yifan; Yang, Junkai; Wang, Huaixiang; Ji, Yu; Guo, Qinwen; Wang, Weipeng; Shen, Xi; Yao, Yuan; Yu, Richeng
Abstract : The effect of antisite defects and their density on monolayer hexagonal boron nitride is discussed in detail. Different supercell sizes to simulate different defect densities are set up. All structures containing antisites are fully optimized. It is indicated that the high density of antisite defects leads to the instability of the BB bond. The influence of supercell size on lattice structure is also summarized. Like vacancies and dopant atoms, the antisite defects also lead to the appearance of the defect energy band. Different antisite defect densities have different effects on different orbitals. Electron energy‐loss spectroscopy theoretical simulation is conducted on a single atom to analyze the influence of antisite defect density on the electronic structure of a single atom. It is shown that the high density of antisite defects makes the σ * transition of B atoms that are far away from the defect more preferred than π * transition, while it has less influence on the transition of central N atoms of the antisite defect NB because of the influence of neighboring atoms. The concentration of antisite defects plays a key role in manipulating the physical properties of monolayer hexagonal boron nitride and is helpful in expanding potential application scenarios. Abstract : Antisite defects in monolayer h ‐BN are discussed. The high density of antisite defects leads to the instability of boronboron bonds and the shift of energy bands. Furthermore, the simulation of electron energy‐loss spectroscopy indicates that the high density of antisite defects makes the σ * transition of boron atoms that are far away from the defect more preferred than the π * transition.